The Joint State Local Government Account and the Crisis of Governance in Nigeria - Etinagbedia, Goodluck; Nwokolobia, Anthony Chukwuemeke (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
This paper explored the problems with the local government's joint account system and their implications for grassroots service delivery. This paper relied on secondary data sourced from books, journals and the Federal Republic of Nigeria's 1999 Constitution. Data collected was analyzed using content analysis method. The paper concluded the State Joint Local Government Account violates the constitution, despite being constitutional, and it also undermines the values of good governance, including accountability, efficiency, transparency, accessibility, and participation. The elimination of the State Joint Local Government Account will allow local governments’ complete financial autonomy and ensure good governance at the local level. The paper therefore among others things advocates for local government's autonomy in the conduct of internal affairs in order to improve the effectiveness of its traditional function as vehicles of social, economic and political advancement at the grassroots